Additive benefits of ß-Alanine supplementation and sprint-interval training - Bellinger, P. M.; Minahan, C. (Medicine & Science in Sports & Exercise, 2016)
Purpose: The present study investigated the effects of ß-alanine supplementation only, and in combination with sprint-interval training (SIT), on training intensity, and energy provision and performance during exhaustive supramaximal-intensity cycling and a 4- and 10-km time trial (TT).